Origin and early diversification of the phylum Cnidaria Verrill: major developments in the analysis of the taxon's Proterozoic–Cambrian history. (21st May 2014) - Van Iten, Heyo; Marques, Antonio C.; Leme, Juliana de Moraes; Pacheco, Mirian L. A. Forancelli; Simões, Marcello Guimaraes; Smith, Andrew
Abstract Diploblastic eumetazoans of the phylum Cnidaria originated during the Neoproterozoic Era, possibly during the Cryogenian Period. The oldest known fossil cnidarians occur in strata of Ediacaran age and consist of polypoid forms that were either nonbiomineralizing or weakly so. The oldest possible anthozoans, including the genus Ramitubus, may be related to tabulate corals and occur in the Doushantuo Lagerstätte (upper Doushantuo Formation, South China), the age of which is poorly constrained (approximately 585 Ma?). Conulariid scyphozoans may first appear as early as 635–577 Ma (Lantian Formation, South China). A definite conulariid, most similar to Palaeozoic species assigned to the genus Paraconularia, occurs in association with the possible scyphozoan, Corumbella werneri, in the latest Ediacaran (c. 543 Ma) Tamengo Formation of Brazil. Basal Cambrian (c. 540 Ma) phosphorites in the upper Kuanchuanpu Formation (South China) yield solitary polyps of the oldest probable anthozoan (Eolympia pediculata), which appears to have been a stem hexacorallian. This same formation contains fossils interpreted by some authors as pentaradial cubozoan polyps; however, both the oldest known cubozoans and the oldest hydrozoans, all medusae, may actually occur in the Cambrian (Series 3, c. 505 Ma) Marjum Formation (Utah, USA). Although these recently published palaeontological data tend to corroborate the hypothesis that Cnidaria has a relatively deep Neoproterozoic history, the timing of major internal branching events remains poorly constrained, with, for example, the results of some molecular clock analyses indicating that the two cnidarian subphyla (Anthozoaria and Medusozoa) may have originated as many as one billion years ago. Further progress towards elucidating the evolution and early fossil record of cnidarians may accrue from: (1) an intensive search for phosphatized soft parts in possible anthozoans from the Ediacaran Doushantuo Formation; (2) an expanded search for Ediacaran conulariids; and (3) additional detailed analyses of the taphonomy and preservation of Ediacaran and Cambrian cnidarians, including possible pentaradial cubozoan polyps from the Fortunian upper Kuanchuanpu Formation.